(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Networks (WSNs) are used in many applications in military, ecological, and health-related areas. These applications often include the monitoring of sensitive information such as enemy movement on the battlefield or the location of personnel in a building. Fault Tolerance is therefore important in WSNs. The reliability of wireless sensor networks (WSNs) is affected by faults that may occur due to various reasons such as malfunctioning hardware, software glitches, dislocation, or environmental hazards. A WSN that is not prepared to deal with such situations may suffer a reduction in overall lifetime, or lead to hazardous consequences in critical application contexts. One of the major fault recovery techniques is the exploitation of redundancy, which is often a default condition in WSNs. Another major approach is the involvement of base stations or other resourceful nodes to maintain operations after failures. We present a selforganizing, singlehop clustering scheme, which is based on partitioning sensor networks into several disjoint cliques. Clustering sensor nodes into small groups is an effective method to achieve fault tolerance, scalability, load balancing, routing etc. Here, each node obtains a list of its neighbour’s connectivity as well as their degree of connection at first. Then, the node with highest degree of connection initiates clique formation process and makes the cluster. Among all the members of the cluster, the node with maximum energy is selected as cluster head (CH).Simulations results obtain so far recovers the faults occurred in the WSN and also provide energy efficient network.